2015
DOI: 10.1037/a0038429
|View full text |Cite|
|
Sign up to set email alerts
|

Maternal regulation of child affect in externalizing and typically-developing children.

Abstract: Temporal contingencies between children's affect and maternal behavior play a role in the development of children's externalizing problems. The goal of the current study was to use a microsocial approach to compare dyads with externalizing dysregulation (N =191) to healthy controls (N = 54) on maternal supportive regulation of children's negative and positive affect. Children were between the ages of 8 and 12 years. Mother-child dyads participated in conflict and positive discussions, and child affect and mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 47 publications
3
49
0
Order By: Relevance
“…Other studies that have examined emotion dynamics in parent-adolescent interactions have utilized a variety of techniques, including state-space grids (e.g., Hollenstein & Lewis, 2006;Lichtwarck-Aschoff et al, 2009), sequential analyses (e.g., Lichtwarck-Aschoff et al, 2010), and event history analysis (e.g., Lougheed, Craig, et al, 2015;Lougheed, Hollenstein, Lichtwarck-Aschoff, & Granic, 2015). Such methods have been crucial for understanding temporal dynamics of emotion in parent-adolescent relationships.…”
Section: Emotion In Parent-adolescent Interactionsmentioning
confidence: 99%
See 3 more Smart Citations
“…Other studies that have examined emotion dynamics in parent-adolescent interactions have utilized a variety of techniques, including state-space grids (e.g., Hollenstein & Lewis, 2006;Lichtwarck-Aschoff et al, 2009), sequential analyses (e.g., Lichtwarck-Aschoff et al, 2010), and event history analysis (e.g., Lougheed, Craig, et al, 2015;Lougheed, Hollenstein, Lichtwarck-Aschoff, & Granic, 2015). Such methods have been crucial for understanding temporal dynamics of emotion in parent-adolescent relationships.…”
Section: Emotion In Parent-adolescent Interactionsmentioning
confidence: 99%
“…Most notably, parental validation (i.e., conveying an understanding of another's thoughts and feelings) and interest (i.e., curiosity about another's point of view and feelings) displayed during parent-adolescent interactions are important for child and adolescent adjustment (Allen, Hauser, Bell, & O'Connor, 1994;Lougheed, Hollenstein, Lichtwarck-Aschoff, & Granic, 2015) and effective conflict resolution (Halpern, 2007). Validation and interest may inhibit destructive and promote constructive behaviors during arguments and downregulate negative emotion (Halpern, 2007).…”
Section: Interpersonal Emotion Dynamicsmentioning
confidence: 99%
See 2 more Smart Citations
“…In other words, mutual empathic communication during conflict that follows a temporal structure is an important feature of successful conflict management in this population. Work by Lougheed et al (2015) using a similar analytic approach (survival analysis) found that parental support (including validation) of children's emotions effectively down-regulates children's negative emotions. In addition to coding interpersonal communication behaviors, some adult research involves participants' continuous ratings of their own emotions and the social partner's behavior (Levenson & Ruef, 1992;Overall, Fletcher, & Kenny, 2012).…”
Section: Empathy Is a Dynamic Processmentioning
confidence: 99%